2018
DOI: 10.3390/ma12010016
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Material Microstructures and Mechanical Properties of AA1100 Aluminum Alloy within a Complex Porthole Die during Extrusion

Abstract: Microchannel tube (MCT) is widely employed in industry due to its excellent efficiency in heat transfer. An MCT is commonly produced through extrusion within a porthole die, where severe plastic deformation is inevitably involved. Moreover, the plastic deformation, which dramatically affects the final property of the MCT, varies significantly from location to location. In order to understand the development of the microstructure and its effect on the final property of the MCT, the viscoplastic self-consistent … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…The reviewed research on dieless drawing for micro-tube fabrication shows that clear advantages of this technology consist in: (a) the possible large degree of cross-section reduction in a single drawing pass, which allows the number of manufacturing steps to be crucially reduced and, with this, production costs; (b) the feasibility to process materials that are difficult to form, but that are of great interest for important fields, such as medical technology; and (c) a comparatively large Achievements in the fabrication of extruded tubular profiles made from aluminum alloys with micro-channels ( Figure 7) by hot extrusion processes involved investigations that led to a deeper understanding of the microstructure evolution during extrusion and of influences on weld seam strength. In [55], a viscoplastic self-consistent model, considering crystal plasticity, together with finite element analysis and a flow line model, was employed to investigate the microstructure evolution during the extrusion process of a micro-channel tube, with ten square channels of a width of 1400 µm. It was found that the rotation of shear planes caused a texture change during the material flow, and relationships between the grain refinement and shear effects were determined [55].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The reviewed research on dieless drawing for micro-tube fabrication shows that clear advantages of this technology consist in: (a) the possible large degree of cross-section reduction in a single drawing pass, which allows the number of manufacturing steps to be crucially reduced and, with this, production costs; (b) the feasibility to process materials that are difficult to form, but that are of great interest for important fields, such as medical technology; and (c) a comparatively large Achievements in the fabrication of extruded tubular profiles made from aluminum alloys with micro-channels ( Figure 7) by hot extrusion processes involved investigations that led to a deeper understanding of the microstructure evolution during extrusion and of influences on weld seam strength. In [55], a viscoplastic self-consistent model, considering crystal plasticity, together with finite element analysis and a flow line model, was employed to investigate the microstructure evolution during the extrusion process of a micro-channel tube, with ten square channels of a width of 1400 µm. It was found that the rotation of shear planes caused a texture change during the material flow, and relationships between the grain refinement and shear effects were determined [55].…”
Section: Discussionmentioning
confidence: 99%
“…When primarily considering the fabrication of seamless metallic tubes, the investigated technologies can be divided into (a) dieless drawing techniques [5,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35], (b) process chains, applying scaled-down and partly modified tube drawing [36][37][38][39][40][41][42][43][44][45][46][47], and (c) manufacturing techniques of grooved micro-tubes for applications in heat exchange [43,[48][49][50][51][52][53][54]. Apart from this research into tube manufacturing processes, notable progress was also achieved in the design of the process and tools for the profile extrusion of tubular micro-profiles with a number of channels [55][56][57][58][59]. Tables 2-5 summarize the details of this research concerning the investigated technologies, micro-tube dimensions, with an outer diameter of d o and tube wall thickness of t, materials, and designated applications in experimental and practical works.…”
Section: Micro-tube Fabricationmentioning
confidence: 99%
See 2 more Smart Citations
“…Multi-port flat tubes (MPFTs) are mostly processed via extrusion, which divides an Al billet into two materials and flows through a porthole die, and rejoins and seam welds them together in the welding chamber. Since the service conditions usually involve inner pressure, the pressure bearing capability is a crucial property of an MPFT [3,4,5,6,7,8]. A high press force is required to ensure the quality of the seam welding zone of an extruded MPFT, which in turn significantly increases the manufacturing cost [9,10].…”
Section: Introductionmentioning
confidence: 99%